Nasopharyngeal Microbiota in Children With Invasive Pneumococcal Disease: Identification of Bacteria With Potential Disease-Promoting and Protective Effects - Camelo-Castillo, Anny; Henares, Desirée; Brotons, Pedro; Galiana, Antonio; Rodríguez, Juan Carlos; Mira, Alex; Muñoz-Almagro, Carmen (Frontiers in Microbiology, 2019)
Background and aims: The risk of suffering from some infectious diseases can be related to specific microbiota profiles. Specifically, the nasopharyngeal microbiota could play a role as a risk or protective factor in the development of invasive disease caused by S. pneumoniae. Methodology: We analyzed the nasopharyngeal microbiota of children with invasive pneumococcal disease (IPD) and that of healthy controls matched by age, sex and seasonality from Catalonia, Spain.Epidemiological, microbiological and clinical variables were considered to compare microbiota profiles, analyzed by sequencing the V1-V4 region of the 16S rRNA gene. Results: Twenty-eight children with IPD (median age 43 months) and 28 controls (42.6 months) were included in the study. IPD children presented a significantly higher bacterial diversity and richness (p<0.001). Principal coordinate analysis revealed three different microbiota profiles: microbiota A, dominated by the genus Dolosigranulum (44.3%); Microbiota B, mostly represented by Streptococcus (36.9%) and Staphylococcus (21.3%) and a high diversity of anaerobic genera including Veillonella, Prevotella and Porphyromonas; and Microbiota C, mainly containing Haemophilus (52.1%) and Moraxella (31.4%). The only explanatory factor for the three microbiotas was the classification of children into disease or healthy controls (p=0.006). A significant negative correlation was found between Dolosigranulum versus Streptococcus (p=0.029), suggesting a potential antagonistic effect against pneumococcal pathogens. Conclusions: The higher bacterial diversity and richness in children with IPD could suggest an impaired immune response. This lack of immune competence could be aggravated by breastfeeding <6 months and by the presence of keystone pathogens such as Porphyromonas, a bacterium which has been shown to be able to manipulate the immune response, and that could favor the overgrowth of many proteolytic anaerobic organisms giving rise to a dramatic dysbiosis.From an applied viewpoint, we found suggestive microbiota profiles associated to IPD or asymptomatic colonization that could be used as disease biomarkers or to pave the way for characterizing health-associated inhabitants of the respiratory tract. The identification of beneficial bacteria could be useful to prevent pneumococcal infections by integrating those microorganisms in a probiotic formula.The present study suggests not only respiratory tract samples, but also breast milk, as a potential source of those beneficial bacteria.